2m(a-b)-3n(b-a)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 06:37:22
2m(a-b)-3n(b-a)2m(a-b)-3n(b-a)2m(a-b)-3n(b-a)2m(a-b)-3n(b-a)=2m(a-b)+3n(a-b)=(a-b)(2m+3n)
2m(a-b)-3n(b-a)
2m(a-b)-3n(b-a)
2m(a-b)-3n(b-a)
2m(a-b)-3n(b-a)
=2m(a-b)+3n(a-b)
=(a-b)(2m+3n)
(a-b)(m-2n)+(b-a)(2m-n)
(A+B)(M-2N)
(-a^m-1b^n-2+3a^m+1b^n)/(-2a^m-2b^n-2)
a(m-n)^2+(n-m)^3 (2)a(a+b)(a-b)-a(a+b)^2
化简(a^m+b^n)(a^2m+b^2n)(a^m-b^n)
2m(a-b)-3n(b-a)
2m(a-b)-3n(b+a)因式分解
2m(a-b)+3n(b-a)怎么作
计算-(m^a*n^b)^2*(m^2*n)^3
(a-b)^m*(a-b)^n*(b-a)^2n*(b-a)^2m+1(m
为正整数)
若(a/b)^n=2,(b/a)^m=3,求(a/b)^2m+3n
m(a+b)+n(a-b)=2a-b配出m,n的值
若m等于-5a+3b,N等于2a-7b,则M+N等于【】,M-N等于【】
若m等于-5a+3b,N等于2a-7b,则M+N等于【】,M-N等于【】
1/27a^(3m-m) -1/3a^(m-n)*b^2n因式分解
已知 m/n=5/3,求m/m+n +m/m-n -n^2/m^2-n^2的值 已知1/a+1/b=8/a+b,求b/a+a/b的值
因式分解:a^(2m+3n)+a^(2m+3n-2)b^2-a^(2m+n)-a^(2m+n-2)b^2+a^(2m-2)b^2+a^2m
因式分解:a^(2m+3n)+a^(2m+3n-2)b^2-a^(2m+n)-a^(2m+n-2)b^2+a^(2m-2)b^2+a^2m